Anti‐Diabetic Agent Sodium Tungstate Induces the Secretion of Pro‐ and Anti‐Inflammatory Cytokines by Human Kidney Cells - Bertinat, Romina; Westermeier, Francisco; Silva, Pamela; Shi, Jie; Nualart, Francisco; Li, Xuhang; Yáñez, Alejandro J. (Journal of cellular physiology, 2017)
Diabetic kidney disease (DKD) is the major cause of end stage renal disease. Sodium tungstate (NaW) exerts anti‐diabetic and immunomodulatory activities in diabetic animal models. Here, we used primary cultures of renal proximal tubule epithelial cells derived from type‐2‐diabetic (D‐RPTEC) and non‐diabetic (N‐RPTEC) subjects as in vitro models to study the effects of NaW on cytokine secretion, as these factors participate in intercellular regulation of inflammation, cell growth and death, differentiation, angiogenesis, development, and repair, all processes that are dysregulated during DKD. In basal conditions, D‐RPTEC cells secreted higher levels of prototypical pro‐inflammatory IL‐6, IL‐8, and MCP‐1 than N‐RPTEC cells, in agreement with their diabetic phenotype. Unexpectedly, NaW further induced IL‐6, IL‐8, and MCP‐1 secretion in both N‐ and D‐RPTEC, together with lower levels of IL‐1 RA, IL‐4, IL‐10, and GM‐CSF, suggesting that it may contribute to the extent of renal damage/repair during DKD. Besides, NaW induced the accumulation of IκBα, the main inhibitor protein of one major pathway involved in cytokine production, suggesting further anti‐inflammatory effect in the long‐term. A better understanding of the mechanisms involved in the interplay between the anti‐diabetic and immunomodulatory properties of NaW will facilitate future studies about its clinical relevance. J. Cell. Physiol. 232: 355–362, 2017. © 2016 Wiley Periodicals, Inc. Sodium tungstate (NaW) exerts anti‐diabetic activities. We further show that NaW induces IL‐6, IL‐8, and MCP‐1 secretion, together with lower levels of IL1‐RA, IL‐4, IL‐10, GM‐CSF in renal proximal tubule epithelial cells from diabetic and non‐diabetic subjects, suggesting that it may contribute to the extent of renal damage/repair of diabetic kidney.